The SoilExp software: An open-source Graphical User Interface (GUI) for post-processing spatial and temporal soil surveys. (September 2020) - Boudoire, G.; Liuzzo, M.; Cappuzzo, S.; Giuffrida, G.; Cosenza, P.; Derrien, A.; Falcone, E.E.
Abstract: Preliminary interpretation of geological processes during field measurement campaigns require fast data analysis to adapt ongoing target strategies. It is the case of soil investigations where coupling geochemical and geophysical records favors a better understanding of subsurface processes. This task requires (i) statistical analysis to identify areas of interest during spatial surveys and (ii) signal processing to analyze temporal series. Here we present SoilExp, an open-source Python-based Graphical User Interface (GUI) that permits to process spatial and temporal surveys of soil gases (e.g. soil CO2 flux) combined with common physical parameters (e.g. self-potential, temperature) that are synchronously recorded on the field. SoilExp mixes innovative algorithms with the more common tools used for the analysis of both spatial surveys or temporal series. It offers the possibility to display distribution plots, maps, comparative plots, spectra and spectrograms, as well as data statistical analysis, in order to deal efficiently with datasets acquired on the field. Field measurements performed at Stromboli (Italy) supports that such software solution facilitates a quick visualization of the data output and is a powerful tool on the geochemical and geophysical analysis. Highlights: Soil gas measurements. Statistical analysis and graphical representation of spatial surveys. Time series analysis, correction and filtering.